2020
DOI: 10.5194/acp-20-13319-2020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of aerosol particles and their optical properties downwind of wildfires in the western US

Abstract: Abstract. During the first phase of the Biomass Burn Operational Project (BBOP) field campaign, conducted in the Pacific Northwest, the DOE G-1 aircraft was used to follow the time evolution of wildfire smoke from near the point of emission to locations 2–3.5 h downwind. In nine flights we made repeated transects of wildfire plumes at varying downwind distances and could thereby follow the plume's time evolution. On average there was little change in dilution-normalized aerosol mass concentration as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 67 publications
10
56
0
Order By: Relevance
“…Compared to previous field measurements of BB, this study reports similar chemical and size evolution after emission, regardless of the combustion phase and emission conditions. There are enhanced compositions of some inorganic species and OA oxidation state (Capes et al, 2008;Pratt et al, 2011;Akagi et al, 2012;Kleinman et al, 2020), decreasing proportions of levoglucosan-like species (Cubison et al, 2011;Forrister et al, 2015;Kleinman et al, 2020) and growing bulk aerosol size (Vakkari et al, 2018). This study demonstrates increasing coatings on BC with transport time, consistent with previous field measurements of higher BC coating thickness as they experienced a longer transport period (e.g.…”
Section: Comparison With Bb Evolution In Other Field Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…Compared to previous field measurements of BB, this study reports similar chemical and size evolution after emission, regardless of the combustion phase and emission conditions. There are enhanced compositions of some inorganic species and OA oxidation state (Capes et al, 2008;Pratt et al, 2011;Akagi et al, 2012;Kleinman et al, 2020), decreasing proportions of levoglucosan-like species (Cubison et al, 2011;Forrister et al, 2015;Kleinman et al, 2020) and growing bulk aerosol size (Vakkari et al, 2018). This study demonstrates increasing coatings on BC with transport time, consistent with previous field measurements of higher BC coating thickness as they experienced a longer transport period (e.g.…”
Section: Comparison With Bb Evolution In Other Field Studiessupporting
confidence: 88%
“…The chemical and size evolution of BB aerosols have been studied comprehensively in field and laboratory measurements under various BB conditions (e.g. Capes et al, 2008;Yokelson et al, 2009;Cubison et al, 2011;Pratt et al, 2011;Akagi et al, 2012;Ortega et al, 2013;Vakkari et al, 2018;Kleinman et al, 2020). However, studies of optical evolution are limited, especially in field observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal values of the weight coefficients are found by minimizing the root mean square difference between the individual values of EnR abs or EnR ext and the corresponding values of y (t e ). Following Konovalov et al (2010), the optimization of the weight coefficients is achieved using the Nelder-Mead simplex algorithm (Press et al, 1992). Although the number of neurons (N) used for the trend approximation can also be optimized in a regular (albeit more complicated) way (Konovalov et al, 2010), here we simply tried the fits with N = 1, N = 2, and N = 3.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Following Konovalov et al (2010), the optimization of the weight coefficients is achieved using the Nelder-Mead simplex algorithm (Press et al, 1992). Although the number of neurons (N) used for the trend approximation can also be optimized in a regular (albeit more complicated) way (Konovalov et al, 2010), here we simply tried the fits with N = 1, N = 2, and N = 3. We found that while the fits with N = 2 manifested statistically significant features that are missing in the approximations with N = 1, the use of three neurons instead of two did not reveal any new statistically significant features of the analyzed trends.…”
Section: Analysis Methodsmentioning
confidence: 99%